Unattached kinetochores drive their own capturing by sequestering a CLASP - Kolenda, Caroline; Ortiz, Jennifer; Pelzl, Marina; Norell, Sarina; Schmeiser, Verena; Lechner, Johannes (Nature Communications, 2018)
Kinetochores (KT) that are not attached to microtubules prevent chromosome missegregation via the spindle assembly checkpoint. Here the authors show that Mps1 localizes Stu1 at unattached KTs together with Slk19, causing a reorganization of the nuclear MT network that favors the capturing of unattached KT.